Regulation of angiotensin type 2 receptor in bovine granulosa cells - Portela, Valerio M.; Goncalves, Paulo B. D.; Veiga, Angela M.; Nicola, Edmir; Buratini, Jose [UNESP]; Price, Christopher A. (Endocrine Soc, 2008)
Angiotensin II (AngII) is best known for its role in blood pressure regulation, but it also has documented actions in the reproductive system. There are two AngII receptors, type 1 (AGTR1) and type 2 (AGTR2). AGTR2 mediates the noncardiovascular effects of AngII and is expressed in the granulosa cell layer in rodents and is associated with follicle atresia. In contrast, expression of AGTR2 is reported to occur only in theca cells in cattle. The objective of the present study was to determine whether AngII also plays a role in follicle atresia in cattle. RT-PCR demonstrated AGTR2 mRNA in both granulosa and theca cells of bovine follicles. The presence of AGTR2 protein was confirmed by immunofluorescence. Abundance of AGTR2 mRNA in granulosa cells was higher in healthy compared with atretic follicles, whereas in theca cells, it did not change. Granulosa cells were cultured in serum-free medium, and treatment with hormones that increase estradiol secretion (FSH, IGF-I, and bone morphogenetic protein-7) increased AGTR2 mRNA and protein levels, whereas fibroblast growth factors inhibited estradiol secretion and AGTR2 protein levels. The addition of AngII or an AGTR2-specific agonist to granulosa cells in culture did not affect estradiol secretion or cell proliferation but inhibited abundance of mRNA encoding serine protease inhibitor E2, a protein involved in tissue remodeling. Because estradiol secretion is a major marker of nonatretic granulosa cells, these data suggest that AngII is not associated with follicle atresia in cattle but may have other specific roles during follicle growth.